SELF CARE IN PATIENTS SUBMITTED TO THE BARIATRIC SURGERY: A CASE STUDY (Fiep Bulletin - online, 2013)
The aim of this study were to characterize the behavior of self-care presented by the patients submitted to the bariatric surgery among the years of 2000 and 2007, in the University Hospital of Maringá (UHM). A descriptive cross sectional study was accomplished. Of the 109 patients submitted the procedure, were located 30 patient, which answered to phone inquiry. The statistical analysis involved measures of central tendency, and when pertinent statistics descriptive were used, beyond accomplishment of non parametric tests and parametric for dependent and independent samples. The bariatric surgery promoted a significant weight reduction from 114,5 (±15,5) to 74,1 (±8,6) with p